BARRIERS ABOUT PHYSICAL EDUCATION COURSE IN THE STATE HIGH SCHOOLS IN KIRŞEHİR - Oğuzhan YONCALIK; Berkan BOZDAĞ (International Journal of Eurasia Social Sciences, 2017)
The purpose of this study is to determine the barriers in front of the realization of physical education course goals in the high schools in Kırşehir city center. The study was carried out with 632 students attending 9 different high schools in Kırşehir in the Fall Semester of 2015-2016 academic year. The 'Physical Education and Sport Facilities and Inadequacies Scale (PESFIS)' developed by the researcher was used as data collection tool. The scale consists of 21 items and 4 sub-dimensions ("institutional inability", "test anxiety and indifference", "student experience" and "infrastructural inadequacies"). As a result, Boys and girls think similar. In terms of the "Institutional disability" sub-dimension, the mean values of the two school groups were close to each other. Science and Anatolian High School students were less concerned about important examinations than General-Fine Arts-Vocational High School students and it was observed that they were more interested in physical education and sports activities. A positive situation was observed in favor of the Science and Anatolian High School students in the Student Experience subdimension including "Problem occurred during physical education and sport activities (messing hair up, sweating, etc)", "Fear of failure", "Negative experiences in the past", " Habits like Internet, TV, playstation, etc.", "mixed education" and "huge class size" items. In the "Infrastructural inadequacies" sub-dimension, General High School-Fine Arts High School-Vocational High School students think more negatively at a significant level than Science and Anatolian High School students.